1975
DOI: 10.1007/bf00384753
|View full text |Cite
|
Sign up to set email alerts
|

Microbodies and glyoxylate-cycle enzyme activities in filamentous fungi

Abstract: Microbodies were observed in the hyphal tips of all 14 fungi investigated. Their morphology varied among the fungi and their numbers were influenced by the growth medium. Microbodies were closely associated with mitochondria in one fungus and with the endoplasmic reticulum in several fungi. Catalase was not detected in microbodies with the diaminobenzidine cytochemical procedure even though catalase activity was present in extracts of these fungi. The activities of the glyoxylate-cycle enzymes isocitrate lyase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
1

Year Published

1977
1977
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 34 publications
5
20
1
Order By: Relevance
“…7) Thisˆnding sharply contrasts with the previously reported ones that either little or no activity of ICL and MS was detected from microorganisms grown in glucose-containing media, [8][9][10][11] because of catabolite repression by glucose. 3,12) Then, we have also demonstrated that MS, which coordinates with malate dehydrogenase generating NADH by oxidation of malate to oxaloacetate, plays a pivotal role in producing oxalate from glucose in the brown-rot fungus Fomitopsis palustris;…”
contrasting
confidence: 74%
“…7) Thisˆnding sharply contrasts with the previously reported ones that either little or no activity of ICL and MS was detected from microorganisms grown in glucose-containing media, [8][9][10][11] because of catabolite repression by glucose. 3,12) Then, we have also demonstrated that MS, which coordinates with malate dehydrogenase generating NADH by oxidation of malate to oxaloacetate, plays a pivotal role in producing oxalate from glucose in the brown-rot fungus Fomitopsis palustris;…”
contrasting
confidence: 74%
“…When expressed in P. infestans, CFP fluorescence localised to small spherical structures throughout the cytoplasm of mycelia and sporangia. They were somewhat heterogeneous in size, with a spatial distribution consistent with peroxisomes observed in electron micrographs of P. ultimum (Maxwell et al 1975). Major differences were not observed between hyphae and sporangia.…”
Section: Fusions With Markers For Subcellular Compartmentsmentioning
confidence: 57%
“…This conclusion is further supported by the distinctive staining characteristics shared by the membranes of the two organelles. Microbodies have also been shown to originate from endoplasmic reticulum in castor bean endosperm (Gonzalez and Beevers 1976), and in filamentous fungi evidence of membrane connections has been indicated in Drechslera sorokiniana (Cole 1973) and Neurospora crassa (Maxwell et al 1975). A third possible role of the compact endoplasmic reticulum in E. pisi is the simultaneous dissociation of all the cisternae of the organelle resulting in the development of the dispersed form.…”
Section: Discussionmentioning
confidence: 95%